High-intensity re-warm-ups enhance soccer performance - Zois, J.; Bishop, D.; Fairweather, I.; Ball, K.; Aughey, R. J. (International Journal of Sports Medicine, 2013)
The effects of high-intensity, short-duration, re-warm-ups on team-sport-related performance were investigated. In a randomised, cross-over study, participants performed 2×26-min periods of an intermittent activity protocol (IAP) on a non-motorized treadmill, interspersed by 15-min of passive recovery (CON); 3-min small-sided game (SSG); or a 5RM leg-press. Measures included counter-movement jump, repeated-sprint, the Loughborough soccer passing test (LSPT), blood lactate concentration, heart-rate, and perceptual measures. Data were analyzed using effect size (90% confidence intervals), and percentage change; determining magnitudes of effects. A 5RM re-warm-up improved flight-time to contraction-time ratio when compared to SSG (9.8%, ES; 0.5±0.3) and CON (ES: 9.4%, 0.7±0.5) re-warm-ups, remaining higher following the second IAP (8.8%, ES; 0.5±0.3 and 10.2%, ES; 0.6±0.6, respectively). Relative-maximum rate-of-force development was greater in the 5RM condition following the second IAP compared to SSG (29.3%, ES; 0.7±0.5) and CON (16.2%, ES; 0.6±0.6). Repeated-sprint ability during the second IAP improved in the 5RM re-warm-up; peak velocity, mean velocity, and acceleration were 4, 3, and 18% greater, respectively. Within groups, the SSG re-warm-up improved LSPT performance post-intervention; 6.4% (ES: 0.6±0.8) and following the second IAP 6.2% (ES: 0.6±0.6), compared to pre-intervention. A 5RM leg-press re-warm-up improved physical performance, while a SSG re-warm-up enhanced skill execution following standardized intermittent exercise.